2019
DOI: 10.1200/jco.19.00108
|View full text |Cite
|
Sign up to set email alerts
|

Pyrotinib or Lapatinib Combined With Capecitabine in HER2–Positive Metastatic Breast Cancer With Prior Taxanes, Anthracyclines, and/or Trastuzumab: A Randomized, Phase II Study

Abstract: PURPOSE Pyrotinib, an irreversible pan-ErbB inhibitor, showed promising antitumor activity and acceptable tolerability in a phase I trial. We assessed the efficacy and tolerability of pyrotinib versus lapatinib, both in combination with capecitabine, in women with human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer in an open-label, multicenter, randomized phase II study. PATIENTS AND METHODS Chinese patients with HER2-positive relapsed or metastatic breast cancer previously treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
317
4
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 256 publications
(336 citation statements)
references
References 20 publications
(23 reference statements)
12
317
4
3
Order By: Relevance
“…Pyrotinib and neratinib are both irreversible ErbB receptor TKIs, which are different in nature from lapatinib, a reversible HER1 and HER2 receptor TKI. Both pyrotinib and neratinib were found to have superior efficacy than lapatinib [5,6]. The median PFS of 11.1 months in PHENIX study achieved by pyrotinib plus capecitabine is comparable to that of 8.8 months achieved by neratinib plus capetabine as third or later line therapy in NALA trial and that of 12.9 months achieved by neratinib plus paclitaxel as first-line treatment in the NEfERT-T trial [6,7], suggesting the potentially comparable efficacy of pyrotinib to neratinib.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Pyrotinib and neratinib are both irreversible ErbB receptor TKIs, which are different in nature from lapatinib, a reversible HER1 and HER2 receptor TKI. Both pyrotinib and neratinib were found to have superior efficacy than lapatinib [5,6]. The median PFS of 11.1 months in PHENIX study achieved by pyrotinib plus capecitabine is comparable to that of 8.8 months achieved by neratinib plus capetabine as third or later line therapy in NALA trial and that of 12.9 months achieved by neratinib plus paclitaxel as first-line treatment in the NEfERT-T trial [6,7], suggesting the potentially comparable efficacy of pyrotinib to neratinib.…”
Section: Introductionmentioning
confidence: 90%
“…Recently pyrotinib, a novel oral pan-ErbB receptor tyrosine kinase inhibitor (TKI), has shown very promising results in metastatic HER2-positive BC [2][3][4][5]. In a phase II study, pyrotinib plus capecitabine had significantly higher objective response rate (ORR) (78.5% vs. 57.1%, p=0.01) and longer progression-free survival (PFS; 18.1 months vs. 7.0 months, p < 0.001) compared to lapatinib plus capecitabine [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing combination treatment of targeted therapies with cytotoxic agents is critical strategy for HER2 + breast cancer. Some studies showed that combination pyrotinib with capecitabine significantly improved PFS and ORR in patients with HER2 + metastatic breast cancer [11,12]. These results revealed the synergistic anticancer activities of pyrotinib plus capecitabine against HER2 + breast cancers.…”
Section: Introductionmentioning
confidence: 84%
“…The gene that encodes HER2 is ampli ed and overexpressed in 15-20% of newly diagnosed breast cancer and results in a worse survival [38,39]. Nevertheless, diverse HER2-directed drugs have signi cantly improved survival in breast cancer patients with HER2-positive subtype [40][41][42][43][44][45]. Even for HER2 positive metastatic breast cancer, anti HER2 therapy also results in considerable and long-lasting improvement in quality of life and overall survival [46].…”
Section: Discussionmentioning
confidence: 99%